(untitled) (Cambridge, UK, 2001)
Anxiety disorders are among the most prevalent mental health problems in childhood. In this timely book, an international team of psychiatrists and psychologists review the most recent theoretical and empirical developments in the field and indicate how these may inform researchers and clinicians. Following a historical introduction, chapters review conceptual and management issues, including cognitive, neurobiological, learning, and developmental processes, and peer group and family influences.
Keywords: Anxiety in children,Lo âu của trẻ em,Adolescent psychotherapy,Tâm lý trị liệu vị thành niên